2004
DOI: 10.1093/intimm/dxh088
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C‐type lectin receptors by subsets of dendritic cells in human skin

Abstract: C-type lectins are cell surface receptors that recognize carbohydrate structures which are often part of microbial pathogens. Several of these molecules are expressed on dendritic cells and are involved in antigen uptake. Expression of C-type lectins on dendritic cells of the human skin, i.e. Langerhans cells of the epidermis and dermal dendritic cells, has been incompletely studied to date. We therefore investigated C-type lectins in situ and on dendritic cells obtained by migration from skin explants by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
3
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 51 publications
11
85
3
1
Order By: Relevance
“…DC-LAMP/ CD208 is a lysosomal protein that specifically marks mature DCs (24). DEC-205/CD205 is a surface receptor that participates in DC antigen endocytosis; its expression increases during maturation, and it has been previously demonstrated in normal human skin (25). The low frequency of CD11c + DCs expressing these 2 antigens observed in normal skin is consistent with their expected immature DC status.…”
Section: Discussionsupporting
confidence: 62%
“…DC-LAMP/ CD208 is a lysosomal protein that specifically marks mature DCs (24). DEC-205/CD205 is a surface receptor that participates in DC antigen endocytosis; its expression increases during maturation, and it has been previously demonstrated in normal human skin (25). The low frequency of CD11c + DCs expressing these 2 antigens observed in normal skin is consistent with their expected immature DC status.…”
Section: Discussionsupporting
confidence: 62%
“…Analysis of the glycolipids derived from ES products showed that they comprise species with Le X and pseudo-Le Y determinants. These ES products that enter the surrounding tissue are good candidate antigens to be encountered by surveying DCs, such as the DC-SIGN positive CD1a negative dermal DCs, which are found mostly in the upper dermis (35,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…8A] . Therefore, these DCs mostly resemble the subepithelial and dermal DCs (17,19,20). We investigated the interaction of DCs with various HIV-1 strains, such as R5-tropic (NL4.3-BaL and JR-CSF), X4-tropic (NL4.3 and 92UG021.6), and gp120-deficient (NL4.3⌬Env) viruses.…”
Section: Hiv-1 Exploits Trypsin-sensitive Molecules Other Than Dc-sigmentioning
confidence: 99%